A dynamic general type-2 fuzzy system with optimized secondary membership for online frequency regulation. (June 2021) - Mohammadzadeh, Ardashir; Sabzalian, Mohammad Hosein; Ahmadian, Ali; Nabipour, Narjes
Abstract: This study suggests a new control system for frequency regulation in AC microgrids. Unlike to the most studies, challenging conditions such as variation of wind speed, multiple load disturbance, unknown dynamics and variable solar radiation are taken to account. To cope with uncertainties, a novel dynamic general type-2 (GT2) fuzzy logic system (FLS) by an optimized secondary membership is suggested. The secondary membership and rule parameters of dynamic GT2-FLS are online tuned through the adaptive optimization rules. The optimization rules are determined such that the robustness and stability to be guaranteed. Also, a new compensator is presented to tackle with estimation error and perturbations. The simulations verify that schemed controller outperforms than conventional methods. Highlights: A general type-2 fuzzy system with optimized secondary membership is presented. The fractional-order tuning laws are presented for secondary membership. A fractional-order controller is proposed for frequency regulation in AC microgrids. The effects of multiple perturbations are investigated. The effect of the estimation errors is compensated by the proposed control system.